Anaplastic pleomorphic xanthoastrocytoma with spinal leptomeningeal spread at the time of diagnosis in an adult. Issue 8 (August 2015) - Benjamin, Carolina; Faustin, Arline; Snuderl, Matija; Pacione, Donato
Abstract We describe the first patient, to our knowledge, with anaplastic pleomorphic xanthoastrocytoma (PXA) with spinal leptomeningeal spread at the time of diagnosis and present a review of the literature. PXA is a tumor that typically has an indolent course but occasionally, when anaplastic features are present, behaves in a more aggressive manner. We found that PXA with spinal leptomeningeal spread at the time of diagnosis confers a worse prognosis. Craniospinal imaging should be obtained at time of diagnosis of PXA and the presence of leptomeningeal spread may be indicative of a more aggressive disease process.